Bohol [videorecording] the period for friendship - Gonzalez, Ibarra M.; Navarro, Christine (The Center, 1997)
Presents cases of LGU-NGO partnership in Bohol with regards to the provinces environment programs. It includes the Panglao Seaweed Farms, the Tarsier Conservation program of Corella, and the mangrove forest protection in Cortez.